The verdict [videorecording (DVD)] - Lumet, Sidney, 1924-2011; Mamet, David; Newman, Paul, 1925-2008; Rampling, Charlotte, 1946-; Warden, Jack; Mason, James, 1909-1984; O'Shea, Milo, 1926-2013; Crouse, Lindsay; Binns, Edward, 1916-1990; Bovasso, Julie; Reed, Barry C. (20th Century Fox Home Entertainment, 2006)
An alcoholic, failed attorney is reduced to ambulance chasing. A friend gives him a supposedly easy malpractice case which becomes a last chance to redeem himself and his career.